Measuring the area green efficiency and the influencing factors in urban agglomeration. (20th December 2019) - Yuan, Wenhua; Li, Jianchun; Meng, Li; Qin, Xiaonan; Qi, Xiaoxing
Abstract: With the rapid development of urbanization and economic growth, urban agglomerations have become an effective way to realize resource sharing and reduce environmental dependence. This paper focuses on the cities within an urban agglomeration and analyzes the spatial characteristics of green development and its influencing factors. Considering the spatial correlation and dependence of green development, this paper proposes a methodology for the spatial analysis of area green efficiency (AGE) and total factor productivity change (TFPC) using a two-level hierarchical framework including diversity and correlation. This approach was tested using an urban agglomeration in China, and the results reveal that AGE varies greatly among cities and that the changing trend is related to the government's regional planning. TFPC presents a significant negative spatial correlation, indicating that the heterogeneity between cities is obvious. The serious problems in the green development of the Shandong Peninsula are due to the improper structure of export products and the insufficient contribution of tertiary industry. Proper policy instruments could improve area green development within an urban agglomeration, including policies promoting closed networks among cities, measures readjusting the industrial structure, and strategies for optimizing the development of tertiary industry according to the characteristics and advantages of each city. Highlights: A methodology is put forward for the spatial analysis of area green development. Area green development in urban agglomeration shows significant spatial correlation. The importance of influencing factors varies in different regions and time periods. Optimizing spatial structure and factor input could improve area green development.